Practical work in physiotherapy students' professional development. Issue 6 (2nd November 2017) - Korpi, Hilkka; Piirainen, Arja; Peltokallio, Liisa
Abstract: Learning practical work through cooperation between school and working life is part of physiotherapy higher education. Students learn practical work through the integration of theoretical, practical, tacit and situational knowledge in a socialization process. Workplace practices and habits direct students' learning. This study answers the question: What kind of conceptions of learning practical work do physiotherapy students have? Longitudinal data written by 21 volunteer students (mean age 25 years) was collected over three and a half years. Thematic analysis was used to analyse the data. Learning practical work proceeds in five phases: (1) the basis of practical work, human movement and action and therapeutic tools is learned at school; (2) the meaning of the profession and practical work takes shape in an interaction with clients and observing how professionals work in real workplaces; (3) the wholeness of the practical work takes shape by gradually participating in the work processes; (4) critical reflection of the work processes – thinking, construction, evaluation and reasoning – develops; and (5) the conception of practical work widens. This study brings new information about learning practical work for developing healthcare education and its curricula. The role of workplaces is huge in learning tacit knowledge of the profession.